‘I want what they’re eating’: College students’ experiences in watching food content on YouTube - Dewa Ayu Mirah Ardrini; Dinar Lubis; Ni Wayan Arya Utami (Universitas Udayana, 2020)
Background and purpose: The prevalence of obesity among adolescents is increasing significantly. One of the predictors of this problem is unhealthy eating pattern due to peer and social media influence. This study aims to explore in depth the experience of college students in watching food content on YouTube. Methods: This study used a qualitative method with a phenomenological approach. Data were obtained through in-depth interviews with ten informants and one focus group discussion with seven female students aged 18-22 years. The informants were female students who have been watching food content on YouTube for more than one year. Data collection was carried out over April-May 2019. Data were analyzed thematically and presented using anarrative approach. Results: There were three themes that emerged in this study, namely the reasons for watching food content, the benefits, and the effects of watching food content on adolescent health habits. Food content on YouTube is imagined to be educational and provides new knowledge related to food and culture in various regions of Indonesia and other countries. Watching YouTube has become a routine teen activity where they can spend one to four hours per day and can cause teens to form sedentary lifestyle. YouTube watching habits are influenced by peers and social media. It can increase adolescent appetite, thus, they more often opt for unhealthy foods. Conclusion: Watching food content on YouTube has a positive and negative impact on adolescent health. One negative impact is that the content or influencers can cause the selection of unhealthy foods. Attractive education method should be applied in order to counteract unhealthy food content and promote healthy eating habits.